Prevalence of HI V-related thrombocytopenia among clients at Mbarara Regional Referral Hospital, Mbarara, southwestern Uganda - Taremwa, Ivan M.; Muyindike, Winnie R.; Muwanguzi, Enoch; Boum, Yap; Natukunda, Bernard (Journal of blood medicine, 2015)
We aimed to determine the prevalence and correlates of thrombocytopenia among people living with human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) and to assess occurrence of antiplatelet antibodies, among thrombocytopenic HIV clients at Mbarara Regional Referral Hospital, southwestern Uganda.This was a retrospective review of hematologic results at enrollment to HIV care from 2005 to 2013.. The prevalence and correlates of thrombocytopenia were estimated based on the Immune Suppressed Syndrome (ISS) Clinic electronic database. A cross-sectional study determined the occurrence of antiplatelet antibodies, using the monoclonal antibody-specific immobilization of platelet antigens (MAIPA) technique.We reviewed 15,030 client records. The median age was 35.0 (range 18–78; interquartile range [IQR] 28–42) years, and there were 63.2% (n=9,500) females. The overall prevalence of thrombocytopenia was 17.4% (95% confidence interval [CI]: 16.8%–18.0%). The prevalence of thrombocytopenia was 17.8% (95% CI: 17.1%–18.4%) among antiretroviral therapy (ART)-naïve clients (n=2,675) and was 13.0% (95% CI: 0.3%–21.9%) for clients who were on ART (n=6). The study found a significant association between thrombocytopenia and other cytopenias, CD4 counts, ART, and deteriorating HIV stage (P,0.05). Two of the 40 participants (5.0%) had antiplatelet antibodies.This study has showed a high prevalence of HIV-related thrombocytopenia. Antiplatelet antibodies were found in 5.0% of HIV-infected thrombocytopenic participants. Our study shows a significant association of thrombocytopenia burden in a high-HIV study population (Southwest Uganda); therefore, there is need to monitor platelet counts and initiate platelet transfusion in our blood banking practices, to avert possible risks of bleeding.
Keywords: antiplatelet antibodies, cytopenia, AIDS